Effect of food on the pharmacokinetics of lurasidone: results of two randomized, open‐label, crossover studies1. (9th September 2013) - Preskorn, Sheldon; Ereshefsky, Larry; Chiu, Yu‐Yuan; Poola, Nagaraju; Loebel, Antony
Abstract : Objective: This study aimed to investigate the effect of prandial status and caloric and fat composition of meals on the pharmacokinetics of lurasidone. Methods: Two randomized, open‐label, crossover studies were conducted in clinically stable adults with schizophrenia or schizoaffective disorder. Study 1 ( n  = 16) evaluated the effect of fasting and three meal types (100 kcal/medium fat, 200 kcal/medium fat, and 800–1000 kcal/high fat), and Study 2 ( n  = 26) evaluated the effect of fasting and five meal types (350 kcal/high fat, 500 kcal/low fat, 500 kcal/high fat, 800–1000 kcal/low fat, and 800–1000 kcal/high fat) on the bioavailability of lurasidone. Subjects received lurasidone 120 mg once daily. Maximum serum concentration ( C max ) and area under the serum concentration–time curve over the dosing interval ( AUC 0–tau ) were determined on Day 5 for each meal type. Results: In Study 1, the geometric mean C max in the fasted state was 56.7 ng/mL compared with 123.0 ng/mL for the 800‐ to 1000‐kcal meal; mean AUC 0–tau was 360.0 versus 752.4 ng·h/mL (both p  < 0.001). Lurasidone exposure following meals containing 100 and 200 kcal was substantially lower than with meals containing 800–1000 kcal. In Study 2, the geometric mean C max was 52.9 ng/mL in the fasted state, 161 ng/mL for the 350‐kcal/high‐fat meal, 135 ng/mL for the 500‐kcal/high‐fat meal, and 131 ng/mL for the 800‐ to 1000‐kcal/high‐fat meal; mean AUC 0–tau was 390, 743, 727, and 769 ng·h/mL, respectively. For all comparisons, the 90% confidence interval of the fed to fasted ratios indicated nonequivalence. Lurasidone exposure was similar following meals containing 350–1000 kcal and was independent of fat content. Conclusion: Lurasidone should be administered with food—at least 350 kcal—to ensure maximum exposure. Copyright © 2013 John Wiley & Sons, Ltd.